2017 12th International Conference for Internet Technology and Secured Transactions (ICITST) 2017
DOI: 10.23919/icitst.2017.8356405
|View full text |Cite
|
Sign up to set email alerts
|

From e-govemment to cloud-government: Challenges of Jordanian citizens' acceptance for public services

Abstract: Abstract-On the inception of the third millennium, there is much evidence that cloud technologies have become the strategic trend for many governments, not only for developed countries (e.g. the UK, Japan and the USA), but also developing countries (e.g. Malaysia and countries in the Middle East region). These countries have launched cloud computing movements for enhanced standardization of IT resources, cost reduction and more efficient public services. Cloud-based e-government services are considered to be o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 19 publications
0
46
0
Order By: Relevance
“…E-Government plays a crucial role in processing information for the management of citizens and businesses by the government [12]. An e-government initiative may include a citizen-centric portal, online income tax, land and property system, e-learning, e-social services, government to employee portal and integrated financial management systems [13]. e-Government has been associated with numerous challenges that make it difficult to be implemented in developing countries.…”
Section: Challenges Of E-governmentmentioning
confidence: 99%
“…E-Government plays a crucial role in processing information for the management of citizens and businesses by the government [12]. An e-government initiative may include a citizen-centric portal, online income tax, land and property system, e-learning, e-social services, government to employee portal and integrated financial management systems [13]. e-Government has been associated with numerous challenges that make it difficult to be implemented in developing countries.…”
Section: Challenges Of E-governmentmentioning
confidence: 99%
“…Similarly, a study by Lal and Bharadwaj [22] focused on integrating an existing e-government system with cloud computing using the TOE model [6]. Martin's et al [9] found that awareness, relative advantage, cultural environment and organisational attitudes have an influence on the intention of organisations to adopt cloud computing [7]. Martin's et al [9] suggested that the measurement of any success of new technologies depends on the context of the system or organisations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…• Top management support: considers how the role of how top management has an important influence on the adoption of cloud computing. Therefore, top management support refers to the role of top managers in supporting decision-making that adopts and implements information technology in order to seek to develop the organisation with technological investments [7]. Based on our literature review concerning the adoption of cloud computing, it is found that top management support is one of the most important factors affecting the adoption of IT at the organisational level [20].…”
Section: A the Organisational Contextmentioning
confidence: 99%
See 2 more Smart Citations